Longmire. The sixth and final season [videorecording (DVD)] - Scott, T. J. (Timothy James); Phillips, Lou Diamond, 1962-; Phillips, Lou Diamond, 1962-; Taylor, Robert, 1963-; Sackhoff, Katee; Freeman, Cassidy, 1982-; Johnson, Craig, 1961- (Warner Bros. Entertainment, 2018)
A sheriff struggles to turn his life around in the wake of his wife's recent passing.